A priori estimated values for conformation characteristics of cation polyelectrolytes - V. M. Komarov; V. S. Kopytin; V. M. Misin; S. S. Nikulin (Тонкие химические технологии)
Conformation characteristics for poly(N,N-dimethyl-N,N-diallylammonia) cloride (PDMDAAC) were calculated basing on isolated Landau&Livshits macromolecule model (using HyperChem program pack) and theoretical model suggested by authors. Obtained results are compared with experimental data for similar to PDMDAAC compounds (polyvinylpirrolydone, poly-L-proline, polyisobutylmaleinimide).